SISTEM PENDUKUNG KEPUTUSAN PENERIMA BANTUAN OPERASIONAL DAERAH (BOSDA) UNTUK SMK NEGERI 2 BANDAR LAMPUNG - Okta Viana; Machudor Yusman; Kurnia Muludi; Aristoteles Aristoteles (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
This research was conducted to create a decision support system for selection of candidates for receiving Regional Operational Assistance (BOSDA) in SMK Negeri 2 Bandar Lampung. Decision support systems are made based on the Web and selection of candidates for BOSDA acceptance using the method (Simple Additive Weighting). The data used from the data of SMK Negeri 2 Bandar Lampung. The selection process for prospective BOSDA recipients is carried out by collecting data on prospective BOSDA recipients along with criteria in accordance with the conditions of prospective BOSDA recipients. Data that has been received is processed by the system by determining the priority of each criterion and summing the weight of each criterion value. The result of system functional testing is that the system is compatible on the computer on the computer being tested and all menus on the system are running well. System testing is performed on the Administration computer SMK Negeri 2 Bandar Lampung. The system test results using Black Box Testing using 220 prospective BOSDA recipient students. Based on testing that has been conducted on users, the system can simplify the performance of the verification team in conducting the selection so that it can run effectively and efficiently. Based on the accuracy of the results of the system decision, it is stated that 87% has met the criteria for selecting potential recipients who are entitled to BOSDA.